Sleep Disturbance, Cognitive Decline, and Dementia: A Review - Wennberg, Alexandra M.V.; Wu, Mark N.; Rosenberg, Paul B.; Spira, Adam P. (Seminars in Neurology, 2017)
Approximately half of older people report sleep disturbances, which are associated with various health conditions, including neurodegenerative disease and dementia. Indeed, 60 to 70% of people with cognitive impairment or dementia have sleep disturbances, which are linked to poorer disease prognosis. Sleep disturbances in people with dementia have long been recognized and studied; however, in the past 10 years, researchers have begun to study disturbed sleep, including sleep fragmentation, abnormal sleep duration, and sleep disorders, as risk factors for dementia. In this review the authors summarize evidence linking sleep disturbance and dementia. They describe how specific aspects of sleep (e.g., quality, duration) and the prevalence of clinical sleep disorders (e.g., sleep-disordered breathing, rapid eye movement sleep behavior disorder) change with age; how sleep parameters and sleep disorders are associated with the risk of dementia; how sleep can be disturbed in dementia; and how disturbed sleep affects dementia prognosis. These findings highlight the potential importance of identifying and treating sleep problems and disorders in middle-aged and older adults as a strategy to prevent cognitive decline and dementia. The authors also review recent evidence linking sleep disturbances to the pathophysiology underlying dementing conditions, and briefly summarize available treatments for sleep disorders in people with dementia.
Keywords: Sleep; aging; dementia